Prioritas Strategi Kesehatan dan Keselamatan Kerja (K3) Menggunakan Metode SAW dan TOPSIS Pada PT PLN Nusantara Power UP Muara Tawar - Muhammad Kamaludin Fasya (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
This study aims to find the highest value of criteria, sub-criteria and alternatives in prioritizing K3 strategies at PLN NP UP Muara Tawar to ensure and protect the workforce. Using the 5M approach (Money, Man, Machine, Methods and Milieu), 21 sub-criteria and 5 alternatives in order to prevent, overcome and minimize the occurrence of work accidents and their impacts by identifying, analyzing and controlling appropriately to improve K3 in the workplace. The Simple Additive Weighting (SAW) mixed method is used to calculate criteria and sub-criteria and Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) calculates alternatives. The results of the analysis show that the highest criterion is man (M) with a score of 0.2113 and the highest sub-criteria are K3 Infrastructure Investment (MO1) and Fire Protection System Infrastructure Investment (MO2) with a score of 0.29577. The highest alternative is with a score of 0.7900 on maintenance of equipment and facilities (A2).